Discover the answers to your questions at Westonci.ca, where experts share their knowledge and insights with you. Get quick and reliable solutions to your questions from knowledgeable professionals on our comprehensive Q&A platform. Our platform provides a seamless experience for finding reliable answers from a network of experienced professionals.

Find [tex]$f^{-1}(-2)$[/tex].

Sagot :

To find [tex]\( f^{-1}(-2) \)[/tex], let's go through the steps of finding the inverse of the function [tex]\( f(x) = 2x - 3 \)[/tex].

1. Start with the function: [tex]\( f(x) = 2x - 3 \)[/tex].

2. Replace [tex]\( f(x) \)[/tex] with [tex]\( y \)[/tex]:
[tex]\[ y = 2x - 3 \][/tex]

3. Solve for [tex]\( x \)[/tex] in terms of [tex]\( y \)[/tex]:
[tex]\[ y + 3 = 2x \][/tex]
[tex]\[ x = \frac{y + 3}{2} \][/tex]

4. Rewrite the inverse function: [tex]\( f^{-1}(y) = \frac{y + 3}{2} \)[/tex].

5. Substitute [tex]\( y = -2 \)[/tex] into the inverse function:
[tex]\[ f^{-1}(-2) = \frac{-2 + 3}{2} \][/tex]
[tex]\[ f^{-1}(-2) = \frac{1}{2} \][/tex]

Thus, the value of [tex]\( f^{-1}(-2) \)[/tex] is [tex]\( \boxed{0.5} \)[/tex].